Ethics of providing clinically assisted nutrition and hydration: current issues - Rochford, Andrew (Frontline Gastroenterol, 2020)
The provision of clinically assisted nutrition and hydration (CANH) often presents clinicians with ethical dilemmas. As the population grows there is increasing prevalence of patients with conditions such as stroke, dementia, advanced malignancy, cerebral palsy and eating disorders and a greater demand for CANH. It is important that healthcare professionals are familiar with the ethical and legal position for the provision of CANH. In addition, it is important to be aware of the clinical indications, relative contraindications and alternative means of supporting patients for whom CANH is not appropriate; this includes education and training for staff, patients, carers and relatives. The lack of high-quality evidence around clinical outcomes, particularly in the form of randomised clinical trials, and the challenges of accurate prognostication in patients who are approaching the end of life make decisions around the provision of CANH difficult for healthcare professionals.